METODE ITERASI AOR UNTUK SISTEM PERSAMAAN LINEAR PREKONDISI - Siswanti '; Syamsudhuha '; Supriadi Putra (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
This article discusses the preconditioner to solve a system of linear equations Ax = b, with A in the form L-matrix, which is a review of articles DJ Evans, et al. [Journal of Computational and Applied Mathematics, 132: 461-466 (2001)]. Analytically we show that the spectral radius of the iteration matrix of the preconditioned AOR method is smaller than the spectral radius of the iteration matrix of a standard AOR method. The analytical results are supported by numerical computations where it appears that the preconditioned AOR method gives fewer number of iterations compare to the standard AOR method in solving given systems of linear equations Ax = b.